Acetophenone derivatives from a freshwater fungal isolate of recently described Lindgomyces madisonensis (G416). (June 2016) - Paguigan, Noemi D.; Raja, Huzefa A.; Day, Cynthia S.; Oberlies, Nicholas H.
Graphical abstract: Seven acetophenone derivatives (1 –7 ), madisone (1 ), 4′-methoxymadisone (2 ), dehydromadisone (3 ), 2″-methoxymadisone (4 ), dihydroallovisnaginone (5 ), dimadisone (6 ), and 4′-methoxydimadisone (7 ) were characterized from an organic extract of recently described Lindgomyces madisonensis (G416) culture. Highlights: Seven acetophenone derivatives were characterized, five of which were previously unknown. These were isolated from a recently desribed strain of Lindgomyces madisonensis. The in situ sampling of a culture of L . madisonensis demonstrated the concentration of the compounds in guttates. Abstract: The exploration of freshwater ascomycetes, which have undergone only limited investigation, may provide opportunities both to characterize new genera/species of fungi and to uncover new chemical diversity. In this study, seven acetophenone derivatives, madisone, 4′-methoxymadisone, dehydromadisone, 2″-methoxymadisone, dihydroallovisnaginone, dimadisone, and 4′-methoxydimadisone were characterized from an organic extract of a recently described Lindgomyces madisonensis (G416) culture, which was isolated from submerged wood collected in a stream in North Carolina. Madisone, dehydromadisone, 2″-methoxymadisone, dimadisone and 4′-demethoxydimadisone have not been reported previously, while 4′-methoxymadisone and dihydroallovisnaginone were previously unknown as natural products. Their structures were assigned on the basis of NMR and HRESIMS data, with the structure of madisone supported by X-ray crystallography. The antimicrobial activities of madisone, 4′-methoxymadisone and dihydroallovisnaginone were evaluated against a panel of bacteria and fungi. A heat map analysis of the surface of a G416 culture showed that most of the isolated compounds concentrated in the guttate compared with the vegetative mycelium of the fungus.